The multilevel effects of transformational leadership on entrepreneurial orientation and service innovation. (September 2019) - Liu, Chih-Hsing Sam; Lee, Tingko
Highlights: We shed insight on the critical attributes of service innovation. We test the mediation role of transformational leadership (TL) and innovation climate. Our hypotheses using data collected from a sample of 95 managers and 475 employees. EO complements TL by instilling an innovation climate that enhance service innovations. Implications for hospitality industry management are discussed.